Mediatization of religion in “texting culture”: self-help religion and the shifting of religious authority - Moch Fakhruroji (Indonesian Journal of Islam and Muslim Societies, 2015)
This  research  is  the  study of SMS Tauhiid phenomena as a  religious practicein  the context of media culture. SMS Tauhiid  service enables  its customer  toaccess  religious messages  through SMS which  is  in particular  contexts  couldpotentially  bring  new  patterns  of  religious  practice. This  article  uses  themediatization  concept  dealing with media  studies  and  political  economy  aswell.  I  argue  that  tausiah  as  (Islamic)  religious  communication  practice havetransformed  into a new pattern  that caused by the accomodative actions thathas taken by the religious leaders and actors against media logics. On the onehand,  this  phenomenon has  opened  a new phase  in disseminating  religiousmessages, however on  the other hand mediatization of  religion has potentialin causing a shift  in the role of religious leaders as the religious authorities.Penelitian ini merupakan studi tentang fenomena SMS Tauhiid sebagai bentukpraktik  agama  dalam  konteks  budaya media.  SMS Tauhiid memungkinkansetiap  pelanggan  dapat mengakses  nasihat  agama melalui  SMS  yang  dalamkonteks  tertentu  berpotensi memunculkan  pola-pola  baru  dalam  beragama.Artikel ini menggunakan pendekatan konsep mediatisasi yang memiliki kaitanerat  dengan  disiplin media  studies  dan  ekonomi  politik.  Saya  berargumen bahwa  tausiah  sebagai  praktik  komunikasi  agama  (Islam)  telah mengalamitransformasi  kedalam  bentuk  baru  disebabkan  tindakan  akomodatif  yangdilakukan  para  tokoh  dan  aktor  agama  terhadap  logika media. Di  satu  sisi,fenomena ini telah membuka babak baru bagi proses penyebaran pesan-pesanagama,  namun  di  sisi  lain mediatisasi  berpeluang menyebabkan  pergeseranperan  tokoh  agama  sebagai  pihak  yang memiliki  otoritas  sumber  informasiagama.